DEPDC5 mutations in genetic focal epilepsies of childhood. Issue 5 (14th April 2014) - Lal, Dennis; Reinthaler, Eva M.; Schubert, Julian; Muhle, Hiltrud; Riesch, Erik; Kluger, Gerhard; Jabbari, Kamel; Kawalia, Amit; Bäumel, Christine; Holthausen, Hans; Hahn, Andreas; Feucht, Martha; et al.
<x xml:space="preserve">Abstract</x> Recent studies reported DEPDC5 loss‐of‐function mutations in different focal epilepsy syndromes. Here we identified 1 predicted truncation and 2 missense mutations in 3 children with rolandic epilepsy (3 of 207). In addition, we identified 3 families with unclassified focal childhood epilepsies carrying predicted truncating DEPDC5 mutations (3 of 82). The detected variants were all novel, inherited, and present in all tested affected (n = 11) and in 7 unaffected family members, indicating low penetrance. Our findings extend the phenotypic spectrum associated with mutations in DEPDC5 and suggest that rolandic epilepsy, albeit rarely, and other nonlesional childhood epilepsies are among the associated syndromes. Ann Neurol 2014;75:788–792